Nutritional Composition, Antioxidant Potential, and Antimicrobial Activity of Selected Wild Edible Fruits from Champadevi Community Forest, Kathmandu, Nepal - Rai, Elina; Bhatt, Lok Ranjan; Joshi, Giri Prasad (Nepal Journal of Botany, 2025)
Wild edible fruits are abundant in the natural environment and found in different parts of Nepal, varying in elevation from low to high lands. The present study aimed to evaluate the nutrient content, antioxidant potential, and antimicrobial activity of fruits of Pyracantha crenulata, Rubus paniculatus, Berberis asiatica, and Myrsine semiserrata collected from Champadevi community forest, Kathmandu. The carbohydrate, protein, and fat content were determined by Clogg-anthrone, Bradford, and Soxhlet extractor methods, respectively. Similarly, antioxidant potential was determined by DPPH radical scavenging assay and antimicrobial activity by agar well diffusion method. All the fruits were found to contain variable amounts of nutrients. The carbohydrate content ranged from 2.4±0.24% (P. crenulata) to 10.64±0.13% (R. paniculatus) of the dry weight of the sample. Fat content ranged from 0.84±0.69% (P. crenulata) to 10.83±0.11% (R. paniculatus), and protein content ranged from 0.08±0.01% (M. semiserrata) to 0.66 ± 0.01% (P. crenulata). Among the tested samples, B. asiatica showed the strongest antioxidant activity, with an IC50 value of 12.03 μg/mL. All the fruit extracts exhibited a zone of inhibition against the tested seven pathogens, while R. paniculatus and M. semiserrata showed a higher zone of inhibition against Candida albicans. The results indicate that wild edible fruits examined in the present study vary in their nutritional composition, antioxidant, and antimicrobial activities.